Treatment of Gastroenteropancreatic Neuroendocrine Tumors with 177Lu-DOTA-TATE: Experience of the Portuguese Institute of Oncology in Porto - Sampaio, Inês Lucena (2016)
Introduction: The purpose of this article is to report the experience of the Portuguese Institute of Oncology - Porto in the treatment of gastroenteropancreatic neuroendocrine tumors with 177Lu-DOTA-TATE, regarding the safety and efficacy of this treatment modality. Material and Methods: A retrospective analysis of clinical reports of patients with gastroenteropancreatic neuroendocrine tumors undergoing treatment with 177Lu-DOTA-TATE between April 2011 and November 2013 was performed. Results: Thirty six cases were reviewed and 30 completed all 3 cycles of 177Lu-DOTA-TATE (83.3%). In these patients it was registered: acute side effects in 8.9% of cycles; grade 3 CTCAE liver toxicity in 13.3% of patients (all with previous abnormal liver function); absence of significant renal or hematologic toxicity; symptomatic improvement in 71.4% of patients; median overall time to progression of 25.6 months; median overall survival from diagnosis of 121.7 months. Patients with higher expression of somatostatin receptors had longer progression-free survival and overall survival times (p < 0.05). Discussion: Peptide receptor radionuclide therapy with 177Lu-DOTA-TATE is an effective, safe and well-tolerated treatment, as evidenced in our study by the following findings: symptomatic improvement in most patients and increased time to disease progression and survival (especially in those with higher sstr expression), with acute and significant subacute/chronic side effects reported only in a minority of cases. Conclusion: Peptide receptor radionuclide therapy with 177Lu-DOTA-TATE is a promising treatment for patients with gastroenteropancreatic neuroendocrine tumors, with demonstrated benefits in terms of safety and efficacy.